Comparison of mother with father of children with cancer in terms of marital intimacy, parental self-efficacy and cognitive emotion regulation strategies - Gharehdaghi , Minoo; Kachooei , Mohsen (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This study was conducted with the aim of comparing mothers and fathers of children with cancer in terms of marital intimacy, parental self-efficacy and emotion regulation strategies. Method: This study was of comparative causal type. Among the parents who referred to Mahak Hospital in Tehran in 2022, 146 people (73 couples) were selected as the current sample and questionnaire of intimacy-marriage (Walker and Thompson, 1983), parental self-efficacy (Dumka et al., 1996) and cognitive emotion regulation strategies (Garnefski & Kraaij, 2006) were completed. Dependent t-test and SPSS-27 software were used to analyze the data. Results: The results showed that the average of marital intimacy and parenting self-efficacy was slightly higher in fathers than in mothers, but this difference was not statistically significant (p